Pengaruh Senam Hatha Yoga terhadap Tekanan Darah pada Pasien Hipertensi di Wilayah Kerja Puskesmas Putri Ayu Kota Jambi Provinsi Jambi - Istianah, Syarifatul; Nurhusna, Nurhusna; Sari, Putri Irwanti (Universitas Batanghari Jambi, 2025)
The aim of this study was to determine the effect of hatha yoga exercise on changes in blood pressure in hypertensive patients. This research is a quantitative research with pre-experimental research, using a one group pretest-posttest design with hatha yoga exercise intervention. A sample of 21 respondents used a purposive sampling technique on hypertensive patients at the Putri Ayu Community Health Center, Jambi City. Analysis of the relationship between variables uses the Wilcoxon test. The research results showed that there was a significant influence between changes in blood pressure in hypertensive patients before and after being given hatha yoga exercises in the working area of the Putri Ayu Health Center, Jambi City.